Beneficiation of an andrassy and mansuli bentonite as a drilling mud material - Irawan, Sonny; Samsuri, Ariffin (2005)
Based on the result of Geological Survey Department Malaysia investigation, the bentonite resources in Sabah is great amount. In order to reduce the overall cost in oilwell drilling and completion, the development of Sabah bentonite as drilling mud material has been initiated. In addition, Sabah bentonite is categorized as not sodium based bentonite. Appropriate beneficiation method is sought to removal some of the impurities in Sabah bentonite. There are two objectives that can be summarized in this study. The first one was to determine optimum beneficiation process. The result obtained after the beneficiation methods showed improvement in cation exchange capacity (CEC), which is about 73.33% to 90.38% increment. The higher CEC value indicates the improvement in water absorption capability of bentonite. The second objective was to determine the performance of bentonite as drilling mud material compare with standard bentonite and API (American Petroleum Institute) Specification 13A, respectively.